A Review of Islamic Economic Law on Religious Tourism Arrangements in South Sulawesi - abdulahanaa, abdulahanaa (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2021)
Religious tourism objects in Indonesia are attractive destinations and have the potential to be fully developed. This study is an analysis of Islamic economic law on the arrangements of religious tourism in Indonesia, especially in South Sulawesi. The research method used to examine this problem is field research, utilizing interview, questionnaire, and observation techniques. This study concludes that there are dimensions of Islamic economic law in setting religious tourism. Although there is a difference of opinion on whether or not religious tourism is allowed, it should be noted that religious tourism provides benefits such as increasing the country’s foreign exchange income and developing the community economy. Thus, it is necessary that the government makes regulations that emphasize the purpose of opening religious tourism to the public, including the rights and obligations of managers and visitors, as well as relevant warnings and signs. The regulations have multiple functions, including to improve the economy, to increase the number of visitors, to guarantee the protection of the right to access while maintaining the teachings of their respective religions, to eliminate doubts about the occurrence of deviations of purpose, and to strengthen inter-religious unity. The concept that can be carried out in managing religious tourism objects of different religions is by making rules that integrate arrangements for the benefit of fostering inter-religious relations so as to create harmony in a Pancasila-based society. In the study of Islamic economic law, the arrangements of religious tourism objects will have an impact on creating harmony between religious communities, increasing people’s income, opening up employment opportunities, and strengthening the unity of the nation and the people.